Bone cements for therapy and regeneration for minimally invasive treatment of neoplastic bone defects. Issue 21 (20th May 2021) - Qu, Yu; Zhuang, Hui; Zhang, Meng; Wang, Yufeng; Zhai, Dong; Ma, Bing; Wang, Xin; Qin, Chen; Huan, Zhiguang; Wu, Chengtie
Abstract : A multifunctional injectable MOF-containing calcium phosphate cement (Co-TCPP/CPC) was prepared for the minimally invasive treatment of neoplastic bone defects. The Co-TCPP/CPC can kill tumor cells and promote vascularization and bone regeneration. Abstract : Although calcium phosphate cements (CPCs) have been clinically used to repair bone defects caused by bone tumor resection, traditional CPCs cannot kill the remaining tumor cells after surgery and prevent cancer recurrence. In this study, a multifunctional injectable metal–organic framework (MOF) cobalt coordinated tetrakis(4-carboxyphenyl)porphyrin (Co-TCPP)-modified calcium phosphate cement (Co-TCPP/CPC) was prepared for the minimally invasive treatment of neoplastic bone defects. The incorporation of Co-TCPP not only retained the good injectability of bone cements, but also shortened the setting time, improved the compressive strength, and endowed them with excellent photothermal properties. The hyperthermia effect induced by the presence of Co-TCPP well induced the therapeutic effect against bone tumors both in vitro and in vivo . Moreover, Co-TCPP/CPC exhibited desirable osteogenesis and angiogenesis by promoting bone and vascular regeneration in vivo . Therefore, the Co-TCPP composite bone cement demonstrated its great potential for bone tumor therapy and tissue regeneration, representing a multifunctional biomaterial for the treatment of neoplastic bone defects.